Answer:
4
Step-by-step explanation:
Step 1: Simplify both sides of the equation.
6−4x=6x−8x−2
6+−4x=6x+−8x+−2
−4x+6=(6x+−8x)+(−2)(Combine Like Terms)
−4x+6=−2x+−2
−4x+6=−2x−2
Step 2: Add 2x to both sides.
−4x+6+2x=−2x−2+2x
−2x+6=−2
Step 3: Subtract 6 from both sides.
−2x+6−6=−2−6
−2x=−8
Step 4: Divide both sides by -2.
−2x−2=−8−2
x=4
here is a link:
https://www.mathpapa.com/algebra-calculator.html?q=6-4x%3D6x-8x-2.
Answer:
Converse of the alternate exterior angle theorem
Step-by-step explanation:
just took the test ;)
Answer:
yes
Step-by-step explanation:
Using the converse of Pythagoras' identity
If the square of the longest side is equal to the sum of the squares of the other 2 sides then the triangle is right.
longest side = 15 , then 15² = 225
9² + 12² = 81 + 144 = 225
Thus the sail is a right triangle.
Answer: 6 i think
Step-by-step explanation: